Endometriosis and adenomyosis in a Mullerian agenesis patient: A delayed presentation - Gautam, Monika; Meenakshi Chauhan,; Vani Malhotra,; Sushila Chaudhary,; Sarika Gautam,; Menka Verma, (Asian Journal of Medical Sciences, 2024)
Mullerian duct anomalies are developmental anomalies resulting from failure in organogenesis, fusion, or the reabsorption of the paired Mullerian ducts. Endometriosis and Mullerian anomalies have a high coincidence rate. Obstructive uterine malformations with functioning endometrium have higher chances of co-incident endometriosis. Continuous bleeding into functional uterine remnants can lead to the formation of hematometra, endometriosis, and adenomyosis. We report a case of primary amenorrhea who reported 18 years after vaginoplasty with pain abdomen due to the presence of endometriosis in bilateral ovaries and adenomyosis in the rudimentary uterine horn.